How do you solve (b + 3) ( b - 6) = 0?

2 Answers
Mar 10, 2017

color(blue)(b=-3), color(red) (b=6)

Explanation:

Set up two equations and solve

color(blue)(b+3=0)
color(blue)(b+cancel3cancel(-3)=0-3
color(blue)(b=-3)

color(red)(b-6=0)
color(red)(b-cancel6cancel(+6)=0+6
color(red)(b=6)

Mar 10, 2017

b = -3, 6

Explanation:

You have to find the values of b that makes the equation (b+3)(b-6) = 0 true.

If you can make one of the results of the parentheses equal to 0, then you know that automatically the whole equation would have a result of 0. In other words, if we can find the value of b that makes (b+3) = 0, then if we multiply 0(b-6), we can automatically get the product of 0. We can apply the same concept to the other set of parentheses.

A number added to its opposite will equal to 0, and in the case of b+3, we know that -3 +3 will equal to 0. Therefore one value of b could be -3.
(-3 + 3)(b-6) = 0
0(b-6) = 0
0 = 0

As for b-6 equaling to 0, we know that 6-6 equals to 0. Therefore, b can also equal to 6.
(b + 3)(6-6) = 0
(b+3)0 = 0
0 = 0